Pengembangan E-Modul Geometri Berbasis Etnomatematika Melalui Eksplorasi Kain Tenun di SMPN 6 Mataram - Destiana Safitri; Amrullah Amrullah; M. Gunawan Supiarmo (Pendidikan Matematika FKIP Universitas Mataram, 2026)
The low level of students’ understanding of geometric concepts and the lack of contextual teaching materialsmake mathematics learning tend to be abstract and less engaging. In addition, mathematics learning inschools is still rarely connected to local culture that is closely related to students’ daily lives. Learning thatintegrates local culture can create a more meaningful learning experience for students. Ethnomathematicsbasede-modules can visualize geometric concepts through cultural exploration as a learning medium. Thisstudy aimed to describe the development and determine the validity of an ethnomathematics-based geometrye-module integrating Sasak culture through woven fabric exploration for seventh-grade students at SMPN 6Mataram. The research employed a Research and Development (R&D) approach using Thiagarajan’s 4Dmodel, consisting of the define, design, develop, and disseminate stages. Data from material and media expertevaluations were analyzed using Aiken’s V formula. The results indicated that the developed e-module washighly valid, with a media validity score of 0.86, a material validity score of 0.82, and an overall averagevalidity score of 0.84. Therefore, the interactive website-based e-module is theoretically highly valid for useas a supplementary teaching material in mathematics learning.